Education on Saving and Transactions in Accordance with Sharia Principles for Students and the Community - Suci Mardiyah; Saru Reza; Hidayat Hidayat; Mohd Winario (Journal of Community Service and Empowerment, 2025)
Sharia financial literacy is a crucial aspect in developing healthy financial behavior in accordance with Islamic values. However, the level of public and student understanding of the concept of saving and transactions based on Sharia principles still needs to be improved. This community service activity aims to increase the knowledge, understanding, and awareness of students and the community regarding the importance of saving and transactions in accordance with Sharia principles. The activity was implemented through a participatory approach, encompassing preparation, educational outreach, interactive discussions, practical simulations, evaluation, and follow-up. The material presented covered the basic concepts of Sharia banking, the importance of saving, Sharia savings products, and the application of Sharia principles in daily financial transactions. The results of the activity showed an increase in participants' understanding of the differences between Sharia and conventional banks, the concept of profit-sharing, and the importance of avoiding transactions containing elements of riba, gharar, and maysir. Furthermore, participants demonstrated high enthusiasm throughout the activity and were more motivated to adopt savings habits and use Sharia financial services. This activity makes a positive contribution to increasing Islamic financial literacy and inclusion and encourages wiser, more responsible financial behavior that aligns with Islamic principles.